(3TQM deY GdCOdIs - (3TQa GdOjf Hf GdJdeSGfis; (3CHh GdeYGdj YHO Gdedc Hf YHO Gddg GdLhGjfj GeGe GdMQejf,J (B487 (3g` s ((3eOQSI GdefGRd s)
(3ChdgG (B:s
(3GdMeO hgh GdKfGA Ydi Gddg HPcQ ChUGa LdGdg hceGdg hGdTcQ gh GdKfGA Ydjg HPcQ CfYGeg hCaVGdg hbO jSJYed GdMeO ehVY GdTcQ s
(3BNQgG (B:s
(3hgPg GdJeeI GdePchQI cGajI ai gPG GdHGH hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdESdGejs